2015
DOI: 10.1016/j.nano.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-targeted magnetic nanoparticles for MRI visualization of brain tumor

Abstract: This work focuses on synthesis and characterization of targeted magnetic nanoparticles as magnetic resonance imaging (МRI) agents for in vivo visualization of gliomas. The authors utilize the fact that high-grade gliomas have extensive areas of necrosis and hypoxia, which results in increased secretion of angiogenesis vascular endothelial growth factor (VEGF). Monoclonal antibodies against vascular endothelial growth factor (mAbVEGF) were covalently conjugated to crosslinked BSA coated ferric oxide (Fe3O4) nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…These may be caused by the PEG coating of the nanoparticles that can improve blood circulation duration and effectively decrease macrophage clearance of nanoparticles by the reticuloendothelial system, the enhanced permeability and retention (EPR) effect of solid tumor, as well as the mAbVEGF tumor targeting effect enhancing tumor accumulation. [44][45][46][47] According to the imaging diagnosis result, NIR irradiation treatment was conducted at 24 hours post-intravenous injection of samples. Intravenous injection of PTX-GHP-VEGF with or without 5-minute NIR irradiation exhibited a significant difference ( Figure 11A).…”
Section: Nir Thermal Imaging Guided Tumor Therapymentioning
confidence: 99%
“…These may be caused by the PEG coating of the nanoparticles that can improve blood circulation duration and effectively decrease macrophage clearance of nanoparticles by the reticuloendothelial system, the enhanced permeability and retention (EPR) effect of solid tumor, as well as the mAbVEGF tumor targeting effect enhancing tumor accumulation. [44][45][46][47] According to the imaging diagnosis result, NIR irradiation treatment was conducted at 24 hours post-intravenous injection of samples. Intravenous injection of PTX-GHP-VEGF with or without 5-minute NIR irradiation exhibited a significant difference ( Figure 11A).…”
Section: Nir Thermal Imaging Guided Tumor Therapymentioning
confidence: 99%
“…It was revealed that BSA coating greatly reduced the toxicity of nanoparticles and that the mitoxantrone drugloaded system exhibited excellent therapeutic potential in vitro. The surface of magnetite cores was directly coated with BSA and further cross-linked to improve colloidal stability [124]. Monoclonal antibodies against vascular endothelial growth factor (mAbVEGF) were covalently conjugated to BSA coating on IONPs, which are promising MRI contrast agents for glioma visualization in brain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several promising nanoparticle-based imaging applications are currently in clinical trials, or expected to be in the near future, including nanoparticles for MRI contrast that target an integrin commonly found on the surface of newly developed vessels, and applying carbon nanotubes as possible x-ray sources for a new type of computed tomography scanner [133]. Nanoparticles with metallic components can be used as biosensors, for imaging capability with CT (such as super-paramagnetic iron oxide) in the attempt to better visualize cancer masses [134]. …”
Section: Nanotechnology As a Tool In Transplant Therapymentioning
confidence: 99%